2011
DOI: 10.2174/156800911793743664
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Vaccines in Phase II/III Clinical Trials: State of the Art and Future Perspectives

Abstract: The topic of this review covers a very important branch of cancer research, cancer vaccination. The growing knowledge in tumor immunology has evolved rapidly, starting from nonspecific generic stimulation of the immune system to more specific approaches based on the availability of tumor antigens. The review covers molecular and cell biology, and pharmaceutical technology of cancer vaccines. Particularly, it is aimed at highlighting the results of cancer vaccines from phase II and III clinical trials, an issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 118 publications
0
36
0
Order By: Relevance
“…A multi-center phase II clinical trial using gp100 peptide with or without IL-2 shows that the gp100 peptide vaccine plus IL-2 group had a significant improvement in centrally verified overall clinical response as compared with the IL-2-only group (16% vs 6%), as well as longer progression-free survival [185]. MAGE-A3 peptide/protein vaccines were also tested in phases II and III clinical trials [186][187][188], but a MAGE-A3 phase III clinical trial failed to meet the projected requirement in patients with resected nonsmall cell lung cancer. Consistent with these clinical development of cancer vaccines, phase I trials using NY-ESO-1 recombinant protein or synthetic peptides have been conducted in melanoma and ovarian cancer patients [189][190][191][192], showing that NY-ESO-1 vaccines can induce antigen-specific immune responses, but are insufficient to eradicate cancer cells.…”
Section: Clinical Development Of Cancer Antigen-based Vaccines and Enmentioning
confidence: 99%
“…A multi-center phase II clinical trial using gp100 peptide with or without IL-2 shows that the gp100 peptide vaccine plus IL-2 group had a significant improvement in centrally verified overall clinical response as compared with the IL-2-only group (16% vs 6%), as well as longer progression-free survival [185]. MAGE-A3 peptide/protein vaccines were also tested in phases II and III clinical trials [186][187][188], but a MAGE-A3 phase III clinical trial failed to meet the projected requirement in patients with resected nonsmall cell lung cancer. Consistent with these clinical development of cancer vaccines, phase I trials using NY-ESO-1 recombinant protein or synthetic peptides have been conducted in melanoma and ovarian cancer patients [189][190][191][192], showing that NY-ESO-1 vaccines can induce antigen-specific immune responses, but are insufficient to eradicate cancer cells.…”
Section: Clinical Development Of Cancer Antigen-based Vaccines and Enmentioning
confidence: 99%
“…Generally, phase I and some phase II clinical trials are performed on patients with advanced disease and after administration of multiple chemotherapy regimens, thus with severe immune-impairment [2]. In heavy tumor-burden patients, the ability of vaccines to generate anti-tumor immune response is strongly limited by numerous tumor-produced immunosuppressive factors (eg, transforming growth factor-β and vascular endothelial growth factor) and immunoregulatory mechanisms (eg, regulatory T cells [Tregs] and myeloid derived suppressor cells) [5].…”
Section: Selection Of Patients and Clinical Trial Response Endpointsmentioning
confidence: 99%
“…Presently, CVs can probably have an important role as adjuvant to traditional therapies in the management of minimal residual disease, in particular for patients who are at high risk to relapse [2]. In this context, a recent randomized phase III study reported by Schuster et al [14] suggests that it would be possible to identify a subgroup of patients with follicular lymphoma in first remission after standard treatment, who may benefit from receiving an anti-Id vaccination [15].…”
Section: Advantages and Drawbacks Of Current Cancer Vaccinesmentioning
confidence: 99%
See 2 more Smart Citations